Behind the Makeup: An Exploration of Sleep Quality and Adaptive Strategies Among Freelance Make-Up Artists (MUAs) in West Java Facing Irregular Work Rhythms - Ayu Mutiara Santanu; Asti Dewi Rahayu Fitrianingsih; Habibah Abidin (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Freelance Make Up Artists (MUAs) in West Java work irregular hours, often starting before dawn or finishing late at night, disrupting circadian rhythms and leading to sleep problems. Working in the informal creative sector also means they lack occupational health protection. Early symptoms of shift-work sleep disorder, physical fatigue, and psychological stress are common, yet limited research explores sleep quality within this profession. Understanding their sleep problems and coping patterns is essential to support MUAs’ well-being and the sustainability of the creative industry. Objective : To explore MUAs’ sleep duration, frequency of sleep disturbances, fatigue-related impacts on performance, and adaptive strategies used to cope with occupational stress. Research Methods / Implementation Methods : This qualitative phenomenological study involved eight freelance MUAs selected purposively, all with at least two years of experience and irregular work schedules. Research was conducted in several West Java regions (Bandung, Tasikmalaya, Subang, Garut) from May–July 2025. Data were collected through in-depth interviews, non-participant observation, and documentation. All interviews were recorded with consent and analyzed thematically using NVivo 12 Pro. Results : MUAs experienced markedly irregular sleep patterns driven by client demands, especially during early-morning traditional wedding bookings. Most reported fragmented sleep, short sleep duration, transient insomnia, and chronic fatigue. Physical complaints included headaches, muscle pain, and menstrual disturbances. Psychologically, MUAs described irritability, emotional instability, and reduced concentration. Emotional strain was aggravated by the dual burden of professional work and home responsibilities. Coping strategies such as napping, caffeine intake, and selectively declining clients were common but only offered short-term relief. Long-term health concerns were frequently expressed, along with a desire for time-management guidance, occupational health education, and community support. The absence of formal protections for informal creative workers worsens their vulnerability despite the sector’s economic growth. Conclusion / Lesson Learned : Freelance MUAs in West Java face significant sleep disruptions and related health impacts due to irregular work hours and lack of occupational safeguards. Their coping strategies are temporary and do not address structural challenges. Cross-sector collaboration involving government, community groups,